Suspicion of a teenager with Duchenne disease in the pediatrics department of Sainte Thérèse De Hinche Hospital - Berley Alphonse; Michelande Elien; Phélès Dagerus (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2023)
Duchenne disease is caused by a deletion of the gene coding for dystrophin. The absence of this protein is responsible for the myonecrosis observed during the evolution of the pathology. It is X-linked recessive which explains its occurrence, especially in boys. The manifestation of the disease begins in 3 years - 5 years, and the life expectancy is 20 years - 30 years. In the classic clinic, we have gait disorders, kyphoscoliosis, pseudo hypertrophy of the calves, and a positive Gower's sign. Cardiorespiratory impairment is often incriminated as the cause of death in these patients. Management is based on physiotherapy and corticosteroid therapy. In the event of a cardio-respiratory manifestation, the use of positive pressure ventilation, and anti-hypertensives such as ACE inhibitors and beta-blockers may be necessary. We will discuss the 10 years old patients who present with the classic symptoms of Duchenne disease and how we managed it in a low-income country.